Transformations - Sexton, Anne; Swan, Barbara (Boston: Houghton Mifflin Company, 1971)
From Pulitzer Prize-winning poet Anne Sexton, this collection of poem-stories is a strange, wondrous retelling of Grimms' fairy tales.
Foreword / Kurt Vonnegut, Jr -- The gold key -- Snow White and the seven dwarfs -- The white snake -- Rumpelstiltskin -- The little peasant -- Godfather Death -- Rapunzel -- Iron Hans -- Cinderella -- One-Eye, Two-Eyes, Three-Eyes -- The wonderful musician -- Red Riding Hood -- The maiden without hands -- The twelve dancing princesses -- The frog prince -- Hansel and Gretel -- Briar Rose (Sleeping Beauty).
Koleksi Sumbangan : Abdul Ghafar Ibrahim (AGI)
Keywords: Fairy tales Poetry; Poems (texts); Poetry